2018
DOI: 10.1186/s12886-018-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pre-operative factors affecting range of optimal vaulting after implantation of 12.6-mm V4c implantable collamer lens in myopic eyes

Abstract: BackgroundTo evaluate clinical factors affecting postoperative vaulting in eyes that had achieved optimal vaulting within the range of 250–750 μm following implantation of 12.6-mm V4c implantable collamer lenses (ICL).MethodsA total of 236 eyes of 236 patients that had achieved optimal vaulting following implantation of a 12.6-mm V4c ICL were retrospectively analyzed. Associations between postoperative vaulting and age, preoperative anterior chamber depth (ACD), preoperative axial length (AL), preoperative whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
5
29
0
2
Order By: Relevance
“…According to our results, neither WTW measured by any instrument nor ACD was a reliable predictor of postoperative vaulting, which was also the consensus of many similar studies [34,35,42]. Lee et al [19] obtained the following regression formula after multivariate linear regression analysis of 236 patients with 12.6-mm crystal implantation: central vault (µm) = − 0.784 + (0.171 × preoperative ACD) + (0.038 × preoperative pupil size) + (0.017 × preoperative AL). Unfortunately, the tting degree of this formula was very low (R 2 = 0.144), only one size of ICL was included in this study, and the axial direction of ICL placement was not considered, which would affect the results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to our results, neither WTW measured by any instrument nor ACD was a reliable predictor of postoperative vaulting, which was also the consensus of many similar studies [34,35,42]. Lee et al [19] obtained the following regression formula after multivariate linear regression analysis of 236 patients with 12.6-mm crystal implantation: central vault (µm) = − 0.784 + (0.171 × preoperative ACD) + (0.038 × preoperative pupil size) + (0.017 × preoperative AL). Unfortunately, the tting degree of this formula was very low (R 2 = 0.144), only one size of ICL was included in this study, and the axial direction of ICL placement was not considered, which would affect the results.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, previous studies have shown that changes in pupil size were associated with postoperative vaulting [27][28][29][30]. Lee et al [19] believed that pupil constriction creates anteroposterior vectors through iris constriction, which exerts pressure on the ICL. Because the V4C ICL has a central hole, pressure equilibrium is quickly achieved between the front and rear surfaces of the ICL, facilitating this process (the fountain effect of "aquaport").…”
Section: Discussionmentioning
confidence: 99%
“…The two eyes with low vaulting were not reoperated, but closer follow-up was performed. The low vaulting observed in two eyes might be due to the smaller pupil diameters, as shown by a previous study [45].…”
Section: Discussionsupporting
confidence: 54%
“…Also, absolute pupil ΔE were correlated with absolute vault ΔE, to investigate whether vault differences could be related to inter-eye differences in postoperative pupil sizes. The absolute vault ΔE were compared to three vault groups (average RE and LE), low vault <250 µm, intermediate/optimal [250; 750] µm and high vault >750 µm 12 and for the three lens sizes (12.6, 13.2 and 13.7) mm using the Kruskal–Wallis test. Statistical analysis was performed using IBM SPSS Statistics V23.0.…”
Section: Methodsmentioning
confidence: 99%
“…7 – 11 Despite the variety of associations put forward, the ability of explaining the vault preoperatively is limited to approximately 40% 9 , 10 and decreases to 14% if the prediction is restricted to an optimal vault range. 12 Several arguments have been presented to justify the limited predictability of the models. Lee et al have argued that the vault may depend on the dampening ability of the ciliary-sulcus complex.…”
Section: Introductionmentioning
confidence: 99%